Legal Capacity and Legal Authority of Adult Age in Indonesia: Medical, Psychological and Islamic Law Perspectives - Isroqunnajah, Isroqunnajah; Hawabi, Agus Iqbal; Khoirot, Umdatul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The determination of the age of majority in civil law and Islamic law is an important and controversial issue. Adulthood is closely related to decision-making and responsibility for what they do, both in the eyes of law and socio-culture. Legal capacity and legal authority are important considerations in regulating whether a person is considered to have the capacity to take legal decisions. This study aims to analyze or measure the concept of age of majority in civil regulations from medical, psychological and Islamic legal perspectives. This research uses empirical legal studies with civil law and Islamic law approaches. Researchers collected data in two ways: in-depth interviews and literature studies. The results showed that the government has set rules summarized in the law in accordance with the area of the legal case at hand. In the context of criminal law, it can refer to the Criminal Code (Criminal Code) while Islamic law can refer to the KHI (Compilation of Islamic Law). Although there is no alignment of age determination in it, so when legal problems arise, because there are indeed differences, including from a medical and psychological point of view. Therefore, it is necessary to standardize the age of maturity for a person to have certain rights and obligations within the state or in the face of law. The results of this study are expected to provide deeper insights into the view of adulthood from the perspective of law, fiqh, and psychology in the context of civil regulations. The implications of this research can be useful in developing legal policies that are more adaptive and inclusive to cultural differences and views in determining a person's legal capacity and legal authority in the realm of civil law.